2013
DOI: 10.1007/s11751-013-0181-8
|View full text |Cite
|
Sign up to set email alerts
|

Success of torsional correction surgery after failed surgeries for patellofemoral pain and instability

Abstract: Torsional deformities of the femur and/or tibia often go unrecognized in adolescents and adults who present with anterior knee pain, and patellar maltracking or instability. While open and arthroscopic surgical techniques have evolved to address these problems, unrecognized torsion may compromise the outcomes of these procedures. We collected a group of 16 consecutive patients (23 knees), with mean age of 17, who had undergone knee surgery before torsion was recognized and subsequently treated by means of rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 24 publications
4
59
0
7
Order By: Relevance
“…Meister and James reported similar findings at 10 years of follow-up 137 . Stevens et al evaluated 16 subjects and reported persistent patellar instability at 5 years after surgery in 43% of patients who had undergone torsional correction following previously failed procedures for the treatment of anterior knee pain and patellar maltracking 138 . Stotts and Stevens, in a study of 59 patients who were managed with tibial derotation osteotomy with intramedullary nail fixation, reported that 23.7% of the patients had persistent knee complaints 2 years postoperatively 129 .…”
Section: Operative Considerationsmentioning
confidence: 99%
“…Meister and James reported similar findings at 10 years of follow-up 137 . Stevens et al evaluated 16 subjects and reported persistent patellar instability at 5 years after surgery in 43% of patients who had undergone torsional correction following previously failed procedures for the treatment of anterior knee pain and patellar maltracking 138 . Stotts and Stevens, in a study of 59 patients who were managed with tibial derotation osteotomy with intramedullary nail fixation, reported that 23.7% of the patients had persistent knee complaints 2 years postoperatively 129 .…”
Section: Operative Considerationsmentioning
confidence: 99%
“…Stevens et al [11] published the success of femoral torsional correction in patients who had developed anterior knee pain and/or patellar instability before skeletal maturity and had failed to improve after one or more knee surgeries. Recent literature has also implicated increased femoral anteversion as a cause for femoroacetabular impingement and labral tear [8, 9, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, наружная ротация боль-шеберцовой кости даже при минимальных движениях КС до 15° способствует механи-ческой деградации латеральной суставной поверхности надколенника (хондромаля-ции), компрессирует основную медиальную Обзоры и дополнительные фасетки [37,40], непо-средственно влияя на вращательные дви-жения надколенника, создаёт условия для ранней нестабильности КС и пателлофемо-рального синдрома.…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified
“…Однако она обусловливает общее формирование биомеханики всей нижней конечности, опосредованно, и на КС [37,40]. В частности, были проанализированы эф-фекты как наружной, так и внутренней ро-тации бедра в пределах 0-20°, что влекло к минимальному увеличению нагрузки на фасетки надколенника.…”
Section: Etiopathogenic Bases For Patellofemoral Arthritis Developmentunclassified